(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
India, a country considered a second populated country inthe world happens to lack in education and this being the cause for itsbackwards. It’s seen as stumbling obstruction towards its achievement inclusivedevelopment. “India has about 550 million people under the age of 25 years outof which only 11% are enrolled in tertiary institutions compared to the worldaverage of 23%.”- Statistics given in a symposium conducted by JazanUniversity.